The C-terminal LCAR of host ANP32 proteins interacts with the influenza A virus nucleoprotein to promote the replication of the viral RNA genome - Wang, F; Sheppard, C; Mistry, B; Staller, E; Barclay, W; Grimes, J; Fodor, E; Fan, H (Oxford University Press, 2022)
The segmented negative-sense RNA genome of influenza A virus is assembled into ribonucleoprotein complexes (RNP) with viral RNA-dependent RNA polymerase and nucleoprotein (NP). It is in the context of these RNPs that the polymerase transcribes and replicates viral RNA (vRNA). Host acidic nuclear phosphoprotein 32 (ANP32) family proteins play an essential role in vRNA replication by mediating the dimerization of the viral polymerase via their N-terminal leucine-rich repeat (LRR) domain. However, whether the C-terminal low-complexity acidic region (LCAR) plays a role in RNA synthesis remains unknown. Here, we report that the LCAR is required for viral genome replication during infection. Specifically, we show that the LCAR directly interacts with NP and this interaction is mutually exclusive with RNA. Furthermore, we show that the replication of a short vRNA-like template that can be replicated in the absence of NP is less sensitive to LCAR truncations compared with the replication of full-length vRNA segments which is NP-dependent. We propose a model in which the LCAR interacts with NP to promote NP recruitment to nascent RNA during influenza virus replication, ensuring the co-replicative assembly of RNA into RNPs.